ANALISIS KESALAHAN PENGGUNAAN EJAAN DAN TANDA BACA PADA KUMPULAN CERPEN KARYA SISWA KELAS IX-B - Salwa Muthia Ajra; Eli Syarifah Aeni; Woro Wuryani (IKIP Siliwangi, 2023)
This research is motivated by the many students who are still wrong in using punctuation when writing an essay. Many of the writings were untidy, imperfect and ambiguous, so the researcher wanted to know the level of punctuation errors experienced by students in class IX-B. This study uses a qualitative method that is descriptive, namely by describing 15 short stories by class IX-B students of SMPN 02 Cililin which have been analyzed on the use of full stop (.), comma (,), punctuation, writing names, writing foreign sentences, and initial writing of sentences. The problem discussed is whether or not the use of punctuation marks is correct in this collection of short stories. The purpose of this study is to find out punctuation errors when writing a short story. Based on the results of the discussion, it is known that there are still many students who have not been able to place punctuation marks properly and correctly, especially in the use of commas, periods, and writing names.